Performance of aerobic granular sludge at variable circulation rate in anaerobic–aerobic conditions - Harun, Hasnida; Nor Anuar, Aznah; Ujang, Zaini; Rosman, Noor Hasyimah; Othman, Inawati (IWA Publishing, 2014)
Aerobic granular sludge (AGS) has been applied to treat a broad range of industrial and municipal wastewater. AGS can be developed in a sequencing batch reactor (SBR) with alternating anaerobic– aerobic conditions. To provide anaerobic conditions, the mixed liquor is allowed to circulate in the reactor without air supply. The circulation flow rate of mixed liquor in anaerobic condition is the most important parameter of operation in the anaerobic-AGS processes. Therefore, this study investigates the effect of circulation rate on the performance of the SBR with AGS. Two identical reactors namely R1 and R2 were operated using fermented soy sauce wastewater at circulation rate of 14.4 and 36.0 l/h, respectively. During the anaerobic conditions, the wastewater was pumped out from the upper part of the reactor and circulated back into the bottom of the reactor for 230 min. A compact and dense AGS was observed in both reactors with a similar diameter of 2.0 mm in average, although different circulation rates were adopted. The best reactor performance was achieved in R2 with chemical oxygen demand removal rate of 89%, 90% total phosphorus removal, 79% ammonia removal, 10.1 g/l of mixed liquor suspended solids and a sludge volume index of 25 ml/g.